2018
DOI: 10.11648/j.ijae.20180304.14
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Product Types and Household Income Contribution in Mhondoro-Mubaira (Zimbabwe)

Abstract: The objective of this research was to examine agricultural product types and their contribution to the household income for communal farmers in Mhondoro-Mubaira area. The study was carried out in the area of Mhondoro-Mubaira, situated in Mashonaland West province of Zimbabwe. The target population samples for the study comprised of communal farmers (N=150) and the extension officers (N=25). According to the results, remittances and gifts (92.66%) are the major contributors of household income for most communal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Farmer households' income in Ubon Ratchathani, Thailand primarily comes from agriculture, especially rice crops, followed by income from additional work (off-farm) [61]. Farmers rely heavily on agricultural businesses as their main source of income, although non-farm activities also play an important role in earning income [62]. Zeeshan et al [63] suggested that by engaging in non-farm businesses, farmers could yield positive gains in agricultural income and consumption expenditure for rural farming households.…”
Section: Farmer Household Incomementioning
confidence: 99%
“…Farmer households' income in Ubon Ratchathani, Thailand primarily comes from agriculture, especially rice crops, followed by income from additional work (off-farm) [61]. Farmers rely heavily on agricultural businesses as their main source of income, although non-farm activities also play an important role in earning income [62]. Zeeshan et al [63] suggested that by engaging in non-farm businesses, farmers could yield positive gains in agricultural income and consumption expenditure for rural farming households.…”
Section: Farmer Household Incomementioning
confidence: 99%